Population characterization of Butia exilata Deble & Marchiori and Butia lallemantii Deble & Marchiori (Arecaceae) using morphometric data (Research, Society and Development, 2022)
The genus Butia, native to South America, comprises 21 species, 20 of which occur in Brazil. The species of this genus are quite polymorphic, presenting intermediate forms, which makes it difficult to understand the taxonomic delimitation. In addition, there is a lack of studies that help in understanding the patterns in relation to genetic variability. The use of morphological characters are important parameters in taxonomic and genetic diversity studies, contributing to conservation and genetic improvement strategies. The objective of this work was to determine and correlate morphometric characteristics of the species Butia exilata Deble & Marchiori and Butia lallemantti Deble & Marchiori. Twelve morphological characters were analyzed in 44 matrices from four populations. Statistical analysis with determination of mean values, variance and Pearson's linear correlation was performed with the help of Genes software. The highest and lowest values ​​of mean and variance of fruit mass, longitudinal fruit diameter, equatorial fruit diameter and mesocarp mass were found in the population of Sarandi (1) and population of Alegrete (4), respectively. The highest number of high correlations was found in the population (1), followed respectively by the population of Manoel Viana (3), São Francisco de Assis (2) and Alegrete (4). Fruit mass, equatorial fruit diameter and mesocarp mass were highly correlated in the four populations analyzed.